2021
DOI: 10.1101/2021.09.29.462282
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SPF: A Spatial and Functional Data Analytic Approach to cell Imaging data

Abstract: The tumor microenvironment (TME), which characterizes the tumor and its surroundings, plays a critical role in understanding cancer development and progression. Recent advances in imaging techniques enable researchers to study spatial structure of the TME at a single-cell level. Investigating spatial patterns and interactions of cell subtypes within the TME provides useful insights into how cells with different biological purposes behave, which may consequentially impact a subject's clinical outcomes. We utili… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In other words, if K i is too large, i.e., w ik gets close to 0, leading to no point being observed resulting in indefined entropy. Provided the sparse observed entropies for each individual, fitting SPI i directly into a model as functional covariates as in (31) is not feasible. Therefore, we utilize the approach proposed by Yao et al (32) to address the sparseness in the observed data through functional principal components (FPC) analysis targeting sparse and irregularly spaced data points.…”
Section: Modelmentioning
confidence: 99%
“…In other words, if K i is too large, i.e., w ik gets close to 0, leading to no point being observed resulting in indefined entropy. Provided the sparse observed entropies for each individual, fitting SPI i directly into a model as functional covariates as in (31) is not feasible. Therefore, we utilize the approach proposed by Yao et al (32) to address the sparseness in the observed data through functional principal components (FPC) analysis targeting sparse and irregularly spaced data points.…”
Section: Modelmentioning
confidence: 99%
“…In recent years, various technologies are being used for probing single-cell spatial biology, for example, multiparameter immunofluorescence ( Bataille et al , 2006 ), imaging mass cytometry ( Ali et al , 2020 ), multiplex immunohistochemistry (mIHC) ( Tan et al , 2020 ; Vu et al , 2021 ) and multiplexed ion beam imaging (MIBI) ( Angelo et al , 2014 ; Seal et al , 2021 ). These technologies, often referred to as multiplex tissue imaging, offer the potential for researchers to explore the basis of many different biological mechanisms.…”
Section: Introductionmentioning
confidence: 99%